INDONESIAN CULTURAL DIMENSION IN LET’S TALK TEXTBOOK FOR JUNIOR HIGH SCHOOL - Nurlayli Yanti (Prologue: Journal on Language and Literature, 2024)
The importance of culture and identity to the curriculum has gradually started to emerge in some schools. As a result, it has developed into a valuable research tool that is indispensable to the study of English language teaching. Many Indonesian English textbooks have been published to fulfill the need of teaching-learning process. Unfortunately, some textbooks are not responsive students’ cultural backgrounds which frequently makes it difficult for them to understand the content. There are several textbooks that are used in every school in Banda Aceh, one of them is Let’s Talk textbook. The purpose of this research is to investigate the extend of the cultural dimension of Let's Talk textbook accommodates the culture of Indonesian students. The data of this research are the contents of Let’s Talk textbook then they were analyzed qualitatively. The result of the research can be drawn that there is only four items of instrument of cultural dimension category that accommodate the culture of Indonesian students. There are product, practice, perspective, and person. Based on the data analysis, it can be concluded that the Let’s Talk textbook presents product higher than other categories of cultural dimension which mostly appears on place of Indonesia.